Combination of potassium oxonate with anti-PD-1 for the treatment of colorectal cancer - Wang, Yuanyuan; Hu, Chenxi; Du, Tianpeng; Li, Jiawen; Hui, Kaiyuan; Jiang, Xiaodong (Frontiers in Oncology, 2025)
IntroductionIdentification of effective therapies for colorectal cancer (CRC) remains an urgent medical need, especially for the microsatellite stable (MSS) phenotype. In our previous study, potassium oxonate (PO), a uricase inhibitor commonly used for elevating uric acid in mice, unexpectedly showed remarkable inhibition of tumor growth when combined with anti-programmed death-1 (PD-1). Further research demonstrated that the combination of potassium oxonate and anti-PD-1 could reprogram the immune microenvironment. This study aimed to explore the anti-tumor effect of PO combined with anti-PD-1, and investigate the impact on the immunosuppressive tumor microenvironment (TME).MethodsWe established a syngeneic mouse model of CRC and divided into groups of control group, single drugs group of PO and anti-PD-1, and the combination group. Use the HE staining, immunohistochemistry (IHC) and TUNEL staining of tumor issues to verify the anti-neoplasm of each group. We also tested the changes of TME through flow cytometry of spleen of mice in each group, as well as the IHC of cytokines.ResultsThe co-therapy of PO and anti-PD-1 showed admirable anti-tumor effect compared with the control group and the single drug groups. The TME were tended to an environment beneficial for killing tumors by enhancing chemotactic factor release, increasing CD8+ T cell infiltration and activation, and decreasing the amount of regulatory T cells. Moreover, IFN-γ and IL-2 secretion were found to be enriched in the tumor TME.ConclusionOur study indicated that combination of PO and anti-PD-1 could synergistically suppress CRC progression and altered the tumor microenvironment in favor of antitumor immune responses.